HEALTH COMMUNICATION IN LOCAL AREA REGARDING DENGUE HEMORRHAGIC FEVER THROUGH THE MAGAZINE - เจะเอาะ, ฟารีดา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The research entitle is health communication in the local area regarding to dengue hemorrhagic fever through the magazine. The objectives are to study the production process of dengue hemorrhagic fever content with communication tool and to study the lesson learn of integrated research and teaching media into knowledge-based for health communication in local area regarding to dengue hemorrhagic fever. This research is a mixed method that using qualitative and quantitative lead. Incidentally, the study applies a research result, which is supported by The Thailand Research Fund (TRF), to enhance learning and to extend the result to the community. As it is discovered: health content production in the local area applies research result utilization works in two-stroke interdependence. First, data processing of original to create a new form that suitable for the target group. Second, content creation for communication tools is knowledge -based on research. Lesson learned from integrating research into teaching and learning to produce magazine that focuses on dengue hemorrhagic fever has a seven-step including, 1) interpreted research, 2) getting to know the community, 3) target analysis, 4) choose communication tool, 5) design content, 6) evaluation, and 7) restore data. These processes that students learn to understand the WELL BEING magazine production that base on research knowledge, community and health communication concept until the magazine has been published. Factors of affect health communication in the local area regarding dengue hemorrhagic fever through the magazine are personality, the local language, etiquette and adaptation, collaboration from the targeted researcher, and ready to learn new things.